2020
DOI: 10.24315/tred.531136
|View full text |Cite
|
Sign up to set email alerts
|

Okullarda Hayat Boyu Öğrenme Kültürüne İlişkin Öğretmen Algıları

Abstract: Öz: Bu çalışmanın amacı okullarda hayat boyu öğrenme kültürüne ilişkin öğretmen algılarını belirlemektir. Araştırma tarama modelinde desenlenmiş olup çalışma grubunu, Sivas il merkezinde bulunan ilkokul, ortaokul ve liselerde görev yapmakta olan öğretmenlerden random örnekleme yöntemiyle belirlenen 479 öğretmen oluşturmaktadır. Veri toplama aracı, okullarda hayat boyu öğrenme kültürü ölçeği (OHBÖKÖ), araştırmacılar tarafından geliştirilmiş olup 6 boyut ve 34 maddeden oluşmaktadır. Araştırma bulgularına göre öğ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 19 publications
0
0
0
1
Order By: Relevance
“…It was seen that the highest mean scores belonged to teachers with 26 and over seniority years about "learning to learn", "social and civic competences" and "sense of initiative and entrepreneurship". Related literature, a significant difference was found in favor of teachers with 16-20 years of seniority (Özdaş, 2019) and 16-24 years of seniority (Doğan and Çalışkan Toyoğlu, 2020), about "learning to learn". Related to the research results on seniority, it can be assumed that these results in favor of 21-25 and 26 and over seniority years are due to the professional experiences of teachers and the high number of student profiles they encounter.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 91%
See 3 more Smart Citations
“…It was seen that the highest mean scores belonged to teachers with 26 and over seniority years about "learning to learn", "social and civic competences" and "sense of initiative and entrepreneurship". Related literature, a significant difference was found in favor of teachers with 16-20 years of seniority (Özdaş, 2019) and 16-24 years of seniority (Doğan and Çalışkan Toyoğlu, 2020), about "learning to learn". Related to the research results on seniority, it can be assumed that these results in favor of 21-25 and 26 and over seniority years are due to the professional experiences of teachers and the high number of student profiles they encounter.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 91%
“…In a study conducted by Özdaş (2019) with high school teachers to reveal the level of acquisition of competences, no difference was found between the views of the participants about "communication in mother tongue ", "learning to learn", "sense of initiative and entrepreneurship" and "cultural awareness and expression". Similarly, in the study concluded by Doğan and Çalışkan Toyoğlu (2020), it was determined that there was no significant difference between pre-services teacher opinions on lifelong learning culture in schools in terms of "communication in mother tongue ", "communication in foreign languages", "mathematical competence and basic competences in science/technology", "digital competence", "learning to learn" and "sense of initiative and entrepreneurship". In addition to these results, in a study conducted by Gencel (2013) with pre-service teachers, a significant difference emerged in favor of female participants in "commu-nication in foreign languages" and "learning to learn"; besides, in favor of males in "mathematical competence and basic competences in science/technology".…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bilginin değişim hızıyla birlikte öğrenme şekilleri günümüzde farklılaşmaya başlamıştır. Öğrenme denildiği zaman artık sadece örgün eğitim kurumlarında geçirilen zaman akla gelmemektedir (Çalışkan Toyoğlu & Doğan, 2020). Günümüzde yaşanan bu değişimlerle örgün eğitim kurumlarında verilen bilgilerin yetersiz olduğu gerçeği ortaya çıkmaya başlamıştır.…”
Section: Hayat Boyu öğRenmenin Tanımı Ve Kapsamıunclassified